Gambaran Faktor Koagulasi dan Jumlah Trombosit pada Pasien Diabetes Melitus Tipe 2: Sebuah Studi Potong Lintang - Alfitri, Maura Salsabila; Decroli, Eva; Rofinda, Zelly Dia; Aprilia, Dinda; Yulia, Dwi; Lailani, Mutia (MEDIA ILMU KESEHATAN, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a growing global health threat, where chronic hyperglycemia and insulin resistance can affect coagulation profiles.Objective: This study aims to examine coagulation factor profiles and platelet counts in T2DM patients. Methods: A descriptive cross-sectional observational study using data from prothrombin time (PT), activated partial thromboplastin time (APTT), international normalized ratio (INR), and platelet counts of T2DM patients admitted to the Internal Medicine Ward of Dr. M. Djamil General Hospital, Padang, in October 2023. Data analysis was performed descriptively using SPSS v26 software. Results: Of the 39 patients analyzed, the distribution of characteristics showed a male predominance of 64.1%, with the largest age group being 45–59 years (48.7%). The most common complication associated with T2DM was chronic kidney disease, identified in 82.1% of the study population. Evaluation of hemostasis parameters showed that APTT was prolonged in 56.4% of patients. Conversely, PT (87.2%), INR (87.2%), and platelet count (66.7%) were within reference ranges. Conclusion: This study found most coagulation parameters normal, but a relatively high proportion had prolonged APTT, underscoring the need for individualized coagulation monitoring in T2DM, especially with renal complications